The effect of boundary slip on transient non-Newtonian blood flows under pulsatile pressure - Khajohnsaksumeth, Nathnarong (Curtin University, 2014)
In this work, we investigate the influence of boundary slip for two pulsatile flow problems. The first problem is considered with the transient axially symmetric flows of fluids through vessels taking into account the Fahraeus-Lindqvist effect. The second problem is on general three-dimensional blood flows in the human right coronary artery. Both analytical and numerical results are presented to show the flow phenomena and the influence of the slip parameter on the flow behaviour.